Penggunaan Bahasa Daerah Generasi Muda Provinsi Maluku Utara dan Papua Barat - Buha Aritonang (Badan Pengembangan dan Pembinaan Bahasa, 2020)
The use of vernacular among the younger generation when writing letters and short massage service (SMS)/ whatsapp (WA) in the family domain is interesting to study. In this paper the study is limited to the problem of using vernacular among the younger generation, especially the younger generation of North Maluku and West Papua is in the family domain when they write letters and SMS/WA messages to speech partners. The objective of this research is to describe the category of language use of the young generation of North Maluku and West Papua when writing letters and SMS/WA with their speech partners. This research method is descriptive qualitative in which the data. The results of the analysis showed that the young generation of North Maluku wrote letters to speech partners (parents, uncle/aunt/aunt, grandparents, siblings (brother/sister), and distant relatives) in vernacular through classified letters. very bad and through SMS/WA classified as not good the young generation of North West Papua wrote a letter to speech partners (parents, uncle/aunt/aunt, grandfather/grandmother, siblings (brother/sister), and distant family) using vernacular, either through letters or SMS/WA are classified as not good.AbstrakPenggunaan bahasa daerah di kalangan generasi muda ketika menulis surat dan short massage service (SMS)/ whatsapp (WA) dalam ranah keluarga menarik untuk dikaji. Dalam tulisan ini kajian dibatasi pada masalah penggunaan bahasa daerah di kalangan generasi muda, khususnya generasi muda Maluku Utara dan Papua Barat dalam ranah keluarga ketika mereka menulis surat dan SMS/WA kepada mitra tutur. Tujuan penelitian mendeskripsikan kategori penggunaan bahasa daerah generasi muda Maluku Utara dan Papua Barat ketika menulis surat dan SMS/WA dengan mitra tuturnya. Metode penelitian ini bersifat deskriptif kualitatif yang datanya dikumpulkan dengan metode penyebaran kuesioner. Hasil analisis menunjukkan bahwa generasi muda Maluku Utara menulis surat kepada mitra tutur (orang tua, paman/tante/bibi, kakek/nenek, saudara (kakak/adik), dan famili jauh) dengan bahasa daerah melalui surat tergolong sangat tidak baik dan melalui SMS/WA tergolong tidak baik. Generasi muda Papua Barat Utara menulis surat kepada mitra tutur (orang tua, paman/tante/bibi, kakek/nenek, saudara (kakak/adik), dan famili jauh) dengan bahasa daerah, baik melalui surat maupun SMS/WA tergolong tidak baik.